ANALISIS SISTEM PENCATATAN PENERIMAAN DAN PENGELUARAN KAS SEBAGAI STRATEGI PENGELOLAAN KAS YANG EFEKTIF PADA PT X - Rahmawati, Mutiara Citra Noviyana; Fitriani, Nurul (Media Mahardhika, 2026)
This study aims to analyze the recording system of cash receipts and disbursements as an effective cash man-agement strategy at PT X. PT X is a manufacturing company that has been a client of KJA AP since 2020. Previously, cash recording was done manually and simp-ly using Excel without clear classification between per-sonal and company funds. After being managed by KJA AP, the recording system still uses Excel but is more structured and accurate due to data verification and transaction classification. The research method used is a qualitative approach with a case study. The results indi-cate that the current system is fairly effective in sup-porting managerial decision-making, although there are still some challenges such as delays and mismatches in transaction evidence. KJA AP conducts physical evi-dence verification, reconfirmation, and transaction clas-sification to address these challenges. To enhance future efficiency, KJA AP plans to develop an integrated digital system as part of an improved cash management strategy.